Anticancer potential of methanolic extracts from Pleurotus species on raji cells and antibacterial activity against Methicillin-Resistant Staphylococcus aureus - Muhammad Evy Prastiyanto; RIZAL MAARIF RUKMANA; DEWI KUNTHY SARASWATI; SRI DARMAWATI; ENDANG TRI WAHYUNI MAHARANI; YANUARITA TURSINAWATI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Prastiyanto ME, Rukmana RM, Saraswati DK, Darmawati S, Maharani ETW, Tursinawati Y. 2020. Anticancer potential of methanolic extracts from Pleurotus species on raji cells and antibacterial activity against Methicillin-Resistant Staphylococcus aureus. Biodiversitas 21: 5644-5649. The aim of this work is to identify the potential effects of methanolic extracts from four species of the Pleurotus genus cultivated in Indonesia on nasopharynx cancer (Raji cell line), and to investigate their antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA). This study investigates four species members of Pleurotus (Pleurotus ostreatus, P. cystidiosus, P. flabellatus, and P. pulmonarius var. stechangii). Dry Samples were extracted with methanol to yield crude extracts. Cytotoxicity screening was conducted using MTT assay of dry extracts, while antibacterial activity was calculated based on the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) using Mueller–Hinton broth, via the microdilution method. Compounds were analyzed using thin-layer chromatography (TLC). P. flabellatus provided the highest yield of dry extract (20.8%) with the lowest value of IC50 (556.226 µg/mL) compared to the three other species investigated. Antibacterial activity was calculated as MIC and MBC values against MRSA by the P. flabellatus extract which reached 6.25 mg/mL and 250 mg/mL, respectively. The result of TLC of the dry extract of P. flabellatus revealed the presence of terpenoids. P. flabellatus has the potential to be developed as both an anti-cancer and an antibacterial agent, especially against Raji cells and MRSA strains. However, further in vivo research and discovery of the modes of action involved are still needed to shed light on these effects. Studies can provide new information about the benefits of Pleurotus as a source of natural anticancer and antibacterial compound.